2021
DOI: 10.1093/pm/pnab232
|View full text |Cite
|
Sign up to set email alerts
|

Brain Asymmetry in Pain Affective Modulation

Abstract: Objective The aim of this study was to characterize the dynamic brain networks underlying the affective modulation of pleasant, unpleasant, and neutral image perception due to painful stimulations in healthy subjects. Methods Forty volunteers, 20 men and 20 women, participated in this study. Brain activity was recorded by 64-channel electroencephalography. After data cleaning, functional brain networks were built using the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the study of brain asymmetry, we cannot forget the processing of pain, inevitably associated with emotional circuits. In this sense, Toutain et al [70] have observed an increase in intra-hemispheric interactions in the left hemisphere in case of a painful sensation, this increase being greater in women. These authors also suggest that emotions can modulate the level of brain asymmetry under pain conditions.…”
Section: Neuropathologies and Brain Asymmetrymentioning
confidence: 94%
“…In the study of brain asymmetry, we cannot forget the processing of pain, inevitably associated with emotional circuits. In this sense, Toutain et al [70] have observed an increase in intra-hemispheric interactions in the left hemisphere in case of a painful sensation, this increase being greater in women. These authors also suggest that emotions can modulate the level of brain asymmetry under pain conditions.…”
Section: Neuropathologies and Brain Asymmetrymentioning
confidence: 94%
“…We conduct a spatio-temporal analysis of the spread of the SARS-CoV-2 virus to health regions in Bahia-Brazil and the apply Motif-Synchronization approach to data sets of SARS-Cov-2 virus cases registered in the year March 2020 through April 2021. Several papers have used a similar approach using the same method in different contexts ( Saba et al, 2018 , Araújo et al, 2018 , da Costa et al, 2021 , Rosário et al, 2015 , Toutain et al, 2021 , Toutain et al, 2020 , Silva et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…More severe sensory–motor and cognitive problems were produced after accidents involving the left hemisphere than those produced in the right one [ 26 ]. In addition, the brain processing of pain, closely related with emotion-related regions, also exhibits an increase in intra-hemispheric correlations in the left hemisphere [ 27 ].…”
Section: Discussionmentioning
confidence: 99%